2012
DOI: 10.1186/1746-6148-8-55
|View full text |Cite
|
Sign up to set email alerts
|

Haemoparasites of free-roaming dogs associated with several remote Aboriginal communities in Australia

Abstract: BackgroundTick-borne haemoparasites Babesia vogeli and Anaplasma platys are common among the free-roaming canine populations associated with Aboriginal communities in Australia, whilst the prevalence of haemoplasmas, which are also suspected to be tick-borne, remained unexplored. The aim of this study was to determine the prevalence of haemoplasma infection in these populations, and to identify any correlation with other haemoparasites. Blood was collected from 39 dogs associated with four Aboriginal communiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 20 publications
(26 reference statements)
4
28
1
Order By: Relevance
“…"Candidatus Mycoplasma haematoparvum" was originally detected and characterized in the blood of a splenectomized dog from the United States with hemic neoplasia (27). Subsequently, the same "Candidatus" species was found in other dogs in the United States (27) and in canids from Brazil (28), Europe (8,(29)(30)(31)(32), and Australia (33)(34)(35). Although ticks, in particular Rhipicephalus sanguineus (the brown dog tick), have been suggested as vectors for canine hemotropic mycoplasma transmission, there are no experimental data to support vector competence by any tick species (8,28,30,32,33,35,36).…”
Section: Discussionmentioning
confidence: 99%
“…"Candidatus Mycoplasma haematoparvum" was originally detected and characterized in the blood of a splenectomized dog from the United States with hemic neoplasia (27). Subsequently, the same "Candidatus" species was found in other dogs in the United States (27) and in canids from Brazil (28), Europe (8,(29)(30)(31)(32), and Australia (33)(34)(35). Although ticks, in particular Rhipicephalus sanguineus (the brown dog tick), have been suggested as vectors for canine hemotropic mycoplasma transmission, there are no experimental data to support vector competence by any tick species (8,28,30,32,33,35,36).…”
Section: Discussionmentioning
confidence: 99%
“…However, roaming behaviour data for dogs in Aboriginal and Torres Strait Islander communities in northern Australia are lacking. These populations pose a risk for the spread of existing infectious diseases, including zoonoses (Barker et al, 2012;Brown et al, 2006;Hii et al, 2012;Meloni et al, 1993;Walton et al, 1999), but also potentially for exotic diseases if an incursion in northern Australia occurs.…”
Section: Introductionmentioning
confidence: 98%
“…Based on our in silico PCR analysis (72) of these universal primers against the different mycoplasma 16S rRNA gene sequences available in the GenBank database, it was demonstrated that depending on the target Mycoplasma spp., these primers produce PCR fragments with sizes of 595 to 620 bp. In addition, these universal primers were successfully used for amplification of the partial 16S rRNA hemoplasma genes in a few published studies (73)(74)(75).…”
Section: Methodsmentioning
confidence: 99%